Teaching learning optimization technique FOPID controlled Cuk and SEPIC converter-based PF rectification - Mishra, Alok Kumar; Das, Soumya Ranjan; Giri, Nimay Chandra; Routray, Sangram Kishore; Syam, Fathy Abdelaziz; Elwakil, Ehab S. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
The foremost cause of harmonic contamination is the ample utilization of loads of non-linear type such as static power converters. Because of this load, the input power factor (PF) decreases heavily as they draw a current of non-sinusoidal in nature. This article gives a general presentation investigation of two PF rectification (PFR) converter (PFRC) geographies: Cuk type and single-ended primary-inductance converter or SEPIC type converter. The average current control (ACC) technique is utilized here. Notwithstanding, for control of output voltage, techniques like conventional proportional integral derivative controller (PIDC) or fractional order proportional integral derivative controller (FOPIDC) are used, and the gains of the controller are calculated using a novel teaching learning optimization technique (TLOT), considering integral time absolute error (ITAE). The analysis of both PFRC acted in Simulink/MATLAB and the estimated converters are studied under consistent and dynamic state conditions. The FOPIDC Cuk PFRC is providing 2.97% of THD compared to other converters.